2016
DOI: 10.1631/jzus.b1600264
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of regulatory T lymphocytes in patients with hepatocellular carcinoma

Abstract: Abstract:We investigated the prognostic role of regulatory T cells (Tregs) in patients with hepatocellular carcinoma (HCC). Relevant evidence regarding prognostic significance of Tregs was systematically searched in MEDLINE and Embase databases. A meta-analysis was performed to compare survival in patients with high or low Tregs level (either in peripheral blood or tumor). Eighteen studies were identified that fulfilled for the eligibility criteria and were included for data synthesis. Our pooled hazard ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
1
16
0
2
Order By: Relevance
“…Two meta-analyses inspecting such studies concluded that the absolute numbers of intratumoral Treg cells, as well as numbers of peripheral Treg cells, may well be correlated with a bad prognosis. 35,36 Taken together this lends strong support to the notion that the adaptive immune system, which is negatively regulated by Treg cells, plays key roles in keeping HCC in check. It is now imperative to identify the mechanisms through which Treg cells are recruited to HCCs, as targeting these mechanisms could offer significant therapeutic opportunities.…”
Section: Regulatory T Cellssupporting
confidence: 60%
“…Two meta-analyses inspecting such studies concluded that the absolute numbers of intratumoral Treg cells, as well as numbers of peripheral Treg cells, may well be correlated with a bad prognosis. 35,36 Taken together this lends strong support to the notion that the adaptive immune system, which is negatively regulated by Treg cells, plays key roles in keeping HCC in check. It is now imperative to identify the mechanisms through which Treg cells are recruited to HCCs, as targeting these mechanisms could offer significant therapeutic opportunities.…”
Section: Regulatory T Cellssupporting
confidence: 60%
“…[ 4 , 5 ] The density of TILs is considered a manifestation of the host immune response against tumor cells. Nowadays, the association between TILs and patients’ clinical outcomes have been investigated in non-small cell lung cancer, [ 6 ] esophageal squamous cell carcinoma, [ 7 ] hepatocellular carcinoma, [ 8 ] and breast cancers, [ 9 ] and so on. Moreover, lots of studies have investigated the prognostic impact of TILs on patients with gastric cancer, but their results were inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a large proportion of existed systematic reviews or meta studies on HCC markers were about serum markers [67, 68], and others were focused on one or a set of genes [69, 70], inflammatory-based markers [71, 72]. Due to the differences across experimental methods, sample size and quality, inconsistent annotation and the methods used for data processing and analysis, it is difficult to do integrated bioinformatics analysis with microarray data from different platforms, and sometimes even the raw data are not available in public databases, so there are very few studies that combined the data form different HCC gene expression profiles [73, 74].…”
Section: Discussionmentioning
confidence: 99%